Beyond Classic Implementation Dimensions: Developing the 25 Early Detection of Tuberculosis Framework for Context-Responsive Tuberculosis Policy Implementation - Spadini Putri; Mansyur Achmad; Ika Sartika; Udaya Madjid (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: TB cases in 2024 in Bekasi City reached 14,788 from previous data that identified an implementation gap in TB control. Six distinct dimensions were identified from NVivo analysis and developed into the TB DINI model, where interagency coordination, digital reporting, and stigma reduction are priorities. Objective: This study intends to describe the implementation of TB treatment policy and the factors that motivated this policy, in addition to an appropriate model for TB management in Bekasi City. Methods: A descriptive qualitative research method was used. Data were collected through observation, document review, and interviews with 15 informants selected using purposive sampling. NVivo triangulation was applied to the six central variables present in the Van Meter and Van Horn model. Results: Four implementation dimensions were identified by cluster analysis using the Van Meter and Van Horn model, with the national target as reference. The policy resources have the most significant impact, as shown by the hierarchy chart. The clustering was further informed by concepts such as governance, bureaucracy, early detection, innovation, and social values from a word frequency analysis. This new dimension made the policy implementation model better suited to the context of Bekasi. Conclusion: The Early Detection of Tuberculosis implementation model is a suitable and strategic intervention for tuberculosis control in Bekasi, given its contextual fit, adaptability, sustainability, and comprehensive planning.